Audit Committee Characteristics and Quality of Financial Reporting In State Corporations in Kenya - Lilian Nabwire Ojuwa; Lucy Wamugo Mwangi (Britain International for Academic Research (BIAR) Publisher, 2023)
The study sought to assess the influence of audit committee characteristics on the quality of financial reporting in state corporations in Kenya. Audit committees are created with a sole purpose of affirming the trust towards the company’ integrity in the hearts of the stakeholders in regard to the internal procedures; the exercise by the committee gives the stakeholders’ confidence in matters oversight assigned to the committee. Specifically, the study sought to examine the effect of audit committee expertise and audit committee independence on quality of financial reporting among state corporations in Kenya. An explanatory research design was employed to attain the study's purpose. The study's target population was the 187 government-owned enterprises in Kenya. A sample of 127 firms was selected using a stratified random sampling. A structured questionnaire was utilized to collect data. The data was analysed through descriptive and inferential statistics using the SPSS software. The findings from the study revealed that audit committee expertise has a significant influence on the quality of financial reporting in state corporations. The findings further revealed that the independence of the audit committee had a significant and positive influence on the quality of financial reporting in state corporations in Kenya. The study concluded that through the independence, and expertise of the audit committees, state corporations in Kenya had better quality of the financial reporting. It is therefore recommended that the government through the respective agencies upholds the independence and expertise of the audit committees in order to enhance their ability to deliver appropriate quality of the financial reporting in the corporations.